Mathematical Representation Ability in terms of Student Self Efficacy Using Canva-assisted CORE Model - Hasyim, Moch. Syaefuddin; Junaedi, Iwan; Waluya, ST Budi (Unnes Journal of Mathematics Education Research, 2023)
This research aims to describe mathematical representation abilities of Class VIII students in the implementation of the CORE learning model assisted by Canva which are reviewed from self-efficacy. The research subjects were students in class VIII C and VIII B of SMP Hasanuddin 5 Semarang. The data source in this research is students, obtained from tests result on students' mathematical representation abilities, self-efficacy dimension questionnaires, and interview. The research results show that there is a positive influence on self-efficacy on mathematical representation abilities, participants' mathematical representation abilities Students in terms of self-efficacy vary, in low, medium, and high categories. Subject with low self-efficacy were 5 (25%), subjects with moderate self-efficacy are 10 (50%), and subjects with self efficacy are 5 (25%).